2021
DOI: 10.1111/2041-210x.13589
|View full text |Cite
|
Sign up to set email alerts
|

Efficient effort allocation in line‐transect distance sampling of high‐density species: When to walk further, measure less‐often and gain precision

Abstract: Line‐transect distance sampling is widely used to estimate population densities using distances of observed targets from transect lines to model detectability. When the target taxa are high density, the frequent measuring of distances may make the method seem impractical. We present a method that improves the efficiency of distance sampling when the target species occurs at high density. Only a proportion of targets are measured to model the detection function, and the time saved on the survey is then used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…One caveat of this approach would be that the detection of many animals is known to be habitat-specific (e.g., Aars et al, 2009; Anderson et al, 2015; Ferguson et al, 2019); thus, the transects used to estimate detection should be representative of the available habitat. Work by Knights et al (2021) has shown that this could be addressed in distance surveys by measuring only a proportion of the targets, where the optimal proportion can be determined when the search time and the time taken to make a detection are known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One caveat of this approach would be that the detection of many animals is known to be habitat-specific (e.g., Aars et al, 2009; Anderson et al, 2015; Ferguson et al, 2019); thus, the transects used to estimate detection should be representative of the available habitat. Work by Knights et al (2021) has shown that this could be addressed in distance surveys by measuring only a proportion of the targets, where the optimal proportion can be determined when the search time and the time taken to make a detection are known.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Knights et al (2021) has shown that this could be addressed in distance surveys by measuring only a proportion of the targets, where the optimal proportion can be determined when the search time and the time taken to make a detection are known.…”
Section: Distancementioning
confidence: 99%
“…conscious sampling design; e.g. Conn et al, 2016; Knights et al, 2021). Simulation experiments are a powerful approach to address the performance of estimators in different contexts and assess optimal survey allocation to assist sampling design decisions (Kéry & Royle, 2016; Zurell et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Line transect distance sampling (Buckland et al, 2001) has been a popular method for estimating the density of tropical animals for decades (e.g., Plumptre, 2000; Silvius et al, 2004). The approach continues to be widely employed because it provides an unbiased estimate of density, does not require significant costs or equipment, and supports the engagement of local people in data collection (Fragoso et al, 2016; Knights et al, 2021). An implicit assumption of line transect sampling is that animals are detected from straight transects.…”
Section: Introductionmentioning
confidence: 99%
“…The random element can lead transects to cross landscape features such as rivers, swamps, dense vegetation, and more. Cutting and surveying these transects can be time‐consuming, expensive, and dangerous (Knights et al, 2021). As a result, observers may skirt around these features and deviate from the straight line.…”
Section: Introductionmentioning
confidence: 99%